Experimental crushing analysis of thermoplastic and hybrid composites. (15th October 2019) - Boria, S.; Belingardi, G.; Fiumarella, D.; Scattina, A.
Abstract: In this work the mechanical properties of composites specimens made of thermosetting and thermoplastic materials are compared. The behaviour of a traditional carbon/epoxy laminate is compared with those of a fully polypropylene composite and of a hybrid composite. The hybrid composite is made by stacking different layers of thermoplastic and thermosetting material. The influence of different production processes, for the hybrid composite, are also investigated. The capability of energy absorption are investigated studying the crushing behaviour of impact attenuators. The impact attenuators made of carbon fibre reinforced plastic exhibit the highest load capability with the highest energy absorption. However, the failure mode is brittle with debris formation. Conversely, a failure mode of plastic crushing is observed in the structures made of fully polypropylene. The experimental tests on the specimen made of hybrid laminates proved a strong influence of the production process of the components on the mechanical properties. In the hybrid laminates, the different chemical properties of the base materials lead to a pre-existing delamination state in the final. The results highlight that curing the thermoplastic material before the compaction with the thermosetting laminates is the best solution to guarantee the highest impact resistance.